Dinuclear Triple‐Stranded Helicates Composed of Tetradentate Ligands with Aluminum(III) Chromophores: Optical Resolution and Multi‐color Circularly Polarized Luminescence Properties. (1st December 2020) - Ono, Toshikazu; Ishihama, Kohei; Taema, Ai; Harada, Takunori; Furusho, Kiyonao; Hasegawa, Masashi; Nojima, Yuki; Abe, Masaaki; Hisaeda, Yoshio
Abstract: New chiroptical chromophores, dinuclear triple‐stranded helicates, composed of tetradentate ligands with aluminum(III) ions, are described. These are synthesized in two steps using inexpensive pyrrole derivatives, hydrazine, and aluminum chloride. These molecular architectures (ALPHY) show multi‐color (cyan, yellow, and orange) photoluminescence in solution and in the solid‐state, which depends on the substituents of the ligands. The photoluminescence quantum yields of helicates were up to 54 %. The right‐handed ( P ) and left‐handed ( M ) helicates are so stable that they do not undergo racemization in some solvents and are mirror images according to circular dichroism and circularly polarized luminescence (CPL) with an absolute luminescence dissymmetry factor ( g lum ) of up to the 10 −3 order. Mixing the different helicates produces white‐light emission with CPL characters. This study offers a glimpse into the potential applications of chromophores with diverse photophysical properties. Abstract : In a set of chiroptical chromophores, dinuclear triple‐stranded helicates, based on tetradentate ligands and Al III ions, the right‐handed ( P ) and left‐handed ( M ) helicates are so stable that they do not undergo racemization. They show multi‐color emission with mirror‐image circularly polarized luminescence (CPL) in solution and the solid‐state. A mixture of different helicates produces white‐light emission with CPL character.